Removal of chemical oxygen demand (COD) and total suspended solid (TSS) using electrocoagulation process for treatment of oleochemical wastewater - Faten Ahada, Mohd Azli; Abdul Aziz, Mohd Azoddein (Institute of Physics Publishing, 2020)
Wastewater from oleochemical industry contains high concentration glycierin, chemical oxygen demand (COD) and total suspended solids (TSS) that can cause environmental pollution if discharged without proper treatment method. Currently, oleochemical industry used reverse osmosis membrane and submerged bed biofilm reactor to treat their wastewater. In this work, other method namely electrocoagulation treatment that capable to achieve a high removal of color, COD, biological oxygen demand (BOD) is employed. The objective of the study is to determine the optimum operating condition such as initial pH (6-9), applied current (4.0-8.0A), type of electrode (aluminium & stainless steel & and retention time (10 - 40 min) on degradation of COD and TSS in wastewater from an oleochemical industry using this process. The experimental results showed that the pollutant removal efficiencies of COD and TSS can be achieved at 62.64% and 66.12% respectively, of the initial concentration of parameters using aluminium electrode at the optimum conditions of pH 7.5, applied current 6 A and reaction time of 30 min. All the findings of the study revealed that treatment of oleochemical wastewater by electrocoagulation process at optimum conditions can be used as a treatment.